MEDICINAL PROPERTIES OF APAMARG (ACHYRANTHES ASPERA LINN.) - Kumar Sharma, Ashwini (International Journal of Ayurveda and Pharma Research, 2015)
The Indian system of medicine, Ayurveda, a medical science practiced for a long time for disease free life. It relies mainly upon the medicinal plants for the management of various diseases. Among these herbs Apamarg (Achyranthes Aspera Linn.) is very important and easily available herb mentioned in Vedic literature and in Atharvaveda, considered as lord of all plants on earth. This medicinal plant found as a weed throughout India up to 900 m. Though almost all of its parts are used in traditional system of medicines, seeds, roots, and shoots are the most important parts, which are used medicinally. The present article gives important information on therapeutic uses, traditional medicinal uses mentioned in various Samhitas and Nighantus, phytochemical and pharmacological properties of modern era.